High-efficiency perovskite photovoltaic system performance by molecular dynamics method: Optimizing electron transport thicknesses, hole transport, and anti-reflector layers of the sustainable energy materials. (May 2023) - Henda, Mouna Ben; Alkanhal, Tawfeeq Abdullah; Rebey, Amor; Musmar, Sa'ed A.; Tlili, Iskander
Abstract: The perovskite solar cell was modeled with the assistance of the molecular dynamics (MD) method to propose a superior configuration for perovskite solar cells and high efficiency for longtime use under severe or unsafe operating conditions. To achieve this aim, several materials and alignments were examined. The whole thickness of this device was kept small enough (≦1 µm). Inorganic materials were used as selective compartments. Perovskite solar cells may have the performance of their photovoltaics improved by optimizing certain parameters. When selecting the materials, several criteria were taken into consideration, including thicknesses, cost, stability, efficiency, and compatibility with wearable Photovoltaic (PV). To model this construction, the electro-physical characteristics of the components were considered, and the findings were compared to those obtained by other studies.